The Liability of Housing Developers for Hidden Defects that Cause Loss to Consumers - Denny Umri Butarbutar; Tan Kamello; Runtung Sitepu; Dedi Harianto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The growth of the housing sector in Indonesia has provided the public with a wide range of housing options; however, in practice, problems still arise in the form of hidden defects that consumers only discover after the handover of the property. These hidden defects may include structural cracks, roof leaks, faulty electrical installations, non-functioning plumbing, or discrepancies between the building’s specifications and those agreed upon. This situation causes losses for consumers and raises legal issues regarding the liability of housing developers. This study aims to analyse the legal framework regarding the liability of housing developers for hidden defects that cause harm to consumers, as well as the forms of legal protection that can be provided to consumers. The research method used is normative legal research employing a statutory approach and a contextual approach. The legal sources consist of primary, secondary, and tertiary legal materials, which were analysed qualitatively. The results of the study indicate that the liability of housing business operators for latent defects is regulated in the Civil Code, Law No. 8 of 1999 on Consumer Protection, and Law No. 1 of 2011 on Housing and Residential Areas. Developers are obliged to guarantee the quality of the buildings they market and are liable to provide compensation if hidden defects cause loss to consumers. Compensation may take the form of building repairs, the provision of a replacement property, a refund of a certain amount of money, or other compensation in accordance with applicable legal provisions. Consumers also have the right to pursue resolution through both litigation and non-litigation channels to obtain redress for the losses they have suffered. Thus, the regulation of the liability of housing business operators plays a vital role in realising legal protection and legal certainty for consumers.